Lychee (Lychee chinensis Sonn.), composition and possible applications (Agro Productividad, 2024)
Objective: to mention the importance of the bioactive compounds and fatty acids (FA) present in lychee, in addition to their possible applications Lychee is a fruit originally from Asia, which has sweet pulp and juice, presents an attractive appearance and pleasant flavor, in addition to high nutritional value, so that it is quite accepted by consumers. Lychee is a great source of bioactive compounds such as tannins and vitamin B1. Because of its functionality, it has various uses as in the preparation of teas and medicinal remedies. Because of the functionality it has, it is important to research this fruit in detail and to find possible applications. Therefore, the objective of this study.